ANALISIS DAN STRATEGI MANAJEMEN JEMBATAN PADA SEGMEN JALAN NASIONAL YETTY-UBRUB-YAMBRA-TOWE HITAM - Vinsensius T Sihotang; Harmonis Rante; Dewi Ana Rusim (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2022)
The Yetty-Ubrub-Yambra-Towe Hitam section is one of the important sections in the Papua region because it is the main route to Jayapura which is the capital of Papua Province and this section is included in the national road section. Beside the developing of road pavements, this segment also needs to be supported by the construction and maintenance of bridges. At some points, adequate bridges have been installed. However, at some points it is not sufficient, even the bridge has been badly damaged and the width is only sufficient for one vehicle. This study aims to analyze the bridge management system that has been carried out and then develop a better bridge management strategy for this section. The research location covers the length of the segment and the analytical method used is qualitative analysis. The results indicate that so far the bridge management has not been implemented properly in this section. Therefore, it is necessary to improve the bridge management system that has been carried out. Some things that need to be improved are strategies including implementation time, inspection process, audit staff, reporting, recording of each bridge and filing of reports.